Long term respiratory sequelae of whooping cough in a nationally representative sample. Issue 6518 (15th February 1986) - Britten, N; Wadsworth, J
Abstract : The long term respiratory consequences of whooping cough in childhood were sought among members of the National Survey of Health and Development. Peak expiratory flow rate was measured when the survey members were 36 years old and seven respiratory symptoms were reported at the same time. Peak expiratory flow rate was slightly reduced in those who had had whooping cough as a child, and this difference became non-significant when other factors were taken into account. Unexpectedly, chronic cough was significantly less likely to be reported by those who had had whooping cough, and this difference remained significant only among men after other factors had been taken into account. This study failed to show a long term detrimental effect of whooping cough on the respiratory system.